Service Recovery and Its Effect on Studentsâ Satisfaction, Trust, and WOM Communication - Harsono, Soni (INTERNATIONAL RESEARCH JOURNAL OF BUSINESS STUDIES, 2018)
This study aims to examine the effect of service recovery, using distributive justice, procedural justice, and interactional justice approaches, on studentsâ satisfaction, trust, and WOM at excellent, flagship and non-flagship private universities in East Java, Indonesia. A total of 240 students participated in this study. Sampling was conducted using convenience sampling technique. Data analysis was done using regression assisted by SPSS and WarpPLS program. The results of this study provide university managers understanding that the low bargaining position perceived by the students has an impact on various aspects of teaching and learning process which eventually leads to the levels of studentsâ satisfaction, trust, and WOM. This study also suggests what should be done in the service recovery policy made by each university to increase the studentsâ satisfaction, trust, and positive WOM.Keywords:Â  Service recovery, Satisfaction, Trust and Word of mouth (WOM)Â https://doi.org/10.21632/irjbs.11.2.93-112